2019
DOI: 10.7554/elife.45807
|View full text |Cite
|
Sign up to set email alerts
|

Possible magneto-mechanical and magneto-thermal mechanisms of ion channel activation in magnetogenetics

Abstract: The palette of tools for perturbation of neural activity is continually expanding. On the forefront of this expansion is magnetogenetics, where ion channels are genetically engineered to be closely coupled to the iron-storage protein ferritin. Initial reports on magnetogenetics have sparked a vigorous debate on the plausibility of physical mechanisms of ion channel activation by means of external magnetic fields. The criticism leveled against magnetogenetics as being physically implausible is based on the spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 108 publications
(141 reference statements)
0
48
0
Order By: Relevance
“…While several groups have reproduced the key observation that a sufficiently strong magnetic field can gate TRPV1 [15][16][17] and TRPV4 18,42 , some theoretical calculations have questioned whether ferritin's magnetic properties are sufficient to actuate the channels by either localized heating or mechanical force 24 , as has been proposed. Additionally, follow-up studies of the TRPV4-ferritin platform by Wang et al 43 , Xu et al 44 , and Kole et al 45 , all using electrophysiological readouts, have been unsuccessful in recapitulating the results by Wheeler et al 18 , leading others to suggest alternative physical mechanisms that may account for the growing body of empiric data 42,46,47 . However, none of these studies proposed a possible chemical mechanism, a possibility that was tested here using chemical inhibitors or quenchers of reactive oxygen species generation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While several groups have reproduced the key observation that a sufficiently strong magnetic field can gate TRPV1 [15][16][17] and TRPV4 18,42 , some theoretical calculations have questioned whether ferritin's magnetic properties are sufficient to actuate the channels by either localized heating or mechanical force 24 , as has been proposed. Additionally, follow-up studies of the TRPV4-ferritin platform by Wang et al 43 , Xu et al 44 , and Kole et al 45 , all using electrophysiological readouts, have been unsuccessful in recapitulating the results by Wheeler et al 18 , leading others to suggest alternative physical mechanisms that may account for the growing body of empiric data 42,46,47 . However, none of these studies proposed a possible chemical mechanism, a possibility that was tested here using chemical inhibitors or quenchers of reactive oxygen species generation.…”
Section: Discussionmentioning
confidence: 99%
“…Barbic performed theoretical modeling of ferritin and found that at high iron loading, clusters of iron spins can exist that generate heating above k B T in the presence of a sufficiently strong magnetic field 46 . This led to the suggestion that a second possible mechanism could be considered in which magnetic fields could gate TRPV1 tethered to ferritin through mechanical actuation, either by diamagnetic repulsion of the cell membrane by ferritin or as a result of an Einstein-de Haas effect 46 . In the latter case, a change in the angular momentum of a ferritin nanoparticle in an AMF translates into rotation of the ferritin nanoparticle, which can apply sufficient torque to gate an adjacent TRPV1 channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If noise arising from precession is more important, the system could instead be driven with a microwave frequency electromagnetic field corresponding to the ferromagnetic resonance frequency of the ferritin. If either of these approaches resulted in quantifiable changes in the / threshold required for magnetogentic actuation, it would not be well explained by other proposed mechanisms (Barbic, 2019).…”
Section: Experiments To Test This Hypothesismentioning
confidence: 99%
“…These studies typically incorporate one or more units of the iron storage protein ferritin into a transient receptor potential vanniloid (TRPV) channel protein. Because the TRPV family is known to trigger calcium influx in response to mechanical and thermal cues, magnetic interactions with ferritin have been presumed to be a source of similar effects (Barbic, 2019). However, cogent critique has cast doubt on these speculated mechanisms (Meister, 2016).…”
Section: Introductionmentioning
confidence: 99%